Aplikasi Mobile Penjualan Makanan Sisa Dengan Geolocation Dan Metode Haversine - Maulana, Dimas Octa; Akbar, Fawwaz Ali; Nurlaili, Afina Lina (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2025)
Food waste is a critical global issue with significant economic and environmental implications. In 2021, approximately 40% of the total global food production, equivalent to 2.5 billion tons, was wasted. This figure marks a notable increase of 1.2 billion tons from the estimated food waste in 2011. Globally, Indonesia ranks second in terms of the highest levels of food waste, with 39.4% of the total waste generated in the country being food waste. This statistic makes food waste the predominant type of waste in Indonesia. This research aims to design and develop a mobile geolocation based application for the sale of surplus food, utilizing the haversine method to facilitate this process. The application is designed to allow users to access the locations of surplus food sellers within a maximum radius of 25 kilometers from their position. The results indicate that the developed application successfully displays the distance between consumers and surplus food sellers. Black box testing successfully ensures that all application functionality runs well. The level of user acceptance of the application is at the acceptable level, and the application grade is B.